Principles of Performance and Financial Management between Islamic Banks and Conventional Banks - Fathoni, Choirul; Jairin, Jairin (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
The name of someone, something, and institution had a certain meaning. A meaning depends so much on someone’s perception to an object. Perception of society to Sharia Bank had an impact to society behavior toward Sharia Bank. There was a gap here between bank and society which had to be acted as a bridge through policy and socialization program. Socialization policy which was planned, adaptive, and interesting could minimize the misperception risk. Socially, the socialization program was the enculturization of sharia bank values ​​process, and it was understood as the form of civil education.